ChemInform Abstract: Ceramic Integration Technologies for Solid Oxide Fuel Cells. Issue 10 (7th March 2013) - Schilm, Jochen; Rost, Axel; Poenicke, Andreas; Kusnezoff, Mihails; Michaelis, Alexander
Abstract Review: 52 refs.